Sustainable Education Efforts Through Digital Platforms: A Case Study of Dreams Foundation in Dompu Regency, West Nusa Tenggara - M. Ahleyani; Ranjiv A.A Sihombing; Ainun Nadhifah (CV. Abhinaya Indo Group, 2025)
Sustainable education is the key to achieving long-term development goals. In the digital era, educational transformation through information technology plays an important role in expanding access and quality of learning. This study examines the strategy of Dreams Foundation, a non-formal education platform in Indonesia, in creating sustainable impacts through the Instagram account @ruangtryout. This study uses a descriptive qualitative approach with social media content analysis and documentation observation. The results of the analysis show that Dreams Foundation optimizes educational content (try out simulations, learning tips, mentoring sessions sharing experiences), facilitates social media interaction and literacy, and carries a social mission in Indonesia to increase access to higher education for the underprivileged with a target SNBT score above 750. This strategy is in line with the guidelines for sustainable education that encourage the active role of institutions in educating the public and strengthening the learning ecosystem of prospective students. In conclusion, Dreams Foundation's digital efforts have approached the principles of sustainable education management, although they need to be developed with a more systematic scale and impact evaluation. Recommendations include increasing the integration of digital services and collaboration with a wider educational ecosystem to be able to reach remote areas of the country.